Geochemical Assessment of Oligocene Limestone for Conceivable Use as Raw Material for Portland Cement in Sangaw Area, Iraqi Kurdistan - Saman Ghareeb; Omer Ahmed; Rezhan Jamil (Tikrit Journal of Pure Science, 2024)
The sedimentary deposit of Oligocene rocks is outcropped in Ashdagh mountain in south of Sulaymaniyah - Sangaw area and characterized by highly calcareous limestone, especially in the lower parts. The rocks of this age are composed of nine formations included Shurau, Sheikh Alas, Planai, Baba, Bajwan, Tarjili, Anah, Azkand, and Ibrahim those are deposited during Oligocene. These formations grouped into three types included basinal, lagoonal and reefal according to depositional environment. The aim of the study is geochemical assessment for limestone rock as major raw material in Portland cement product. The study based on XRF chemical composition analysis and loss on ignition for thirty-eight handpicked samples of the area and evaluation of major oxides as Portland cement raw material. The chemical results showed that the tested limestone samples are overwhelmingly composed of calcareous limestone. The chemical investigation appears that the entire progression is comprise of calcareous limestone, which comprises loss on ignition averagely above 42.9% and mostly less than 1% in MgO, Fe2O3 and Al2O3. The limestone classified as high-grade limestone according to the analysis results, which is exceptionally appropriate for Portland cement producing. Geochemical results of samples specified that the limestone contains high ratio of LOI, which it ranges between (38.7% to 43.9%), and other major oxides are in suitable range while alkali metal oxides and SO3 are present in traces. The ratios of the silica modulus (SM), alumina modulus (AM), and lime saturation Factor (LSF) were calculated. It was found that these proportions of examples are mostly consistent with Iraqi Standard Specifications for Portland cement by adding silica, aluminium and iron oxides. The lime saturation factors (LSF) of assessed samples have extensively differing values, but most values have above the limits required for high quality cement. The overall outcomes confirmed that the Oligocene limestone could be use as major raw material for clinker production in cement industry.